Development Response and Production of Tosakan (Brassica Juncea L) Mustard Varieties Application of Liquid Organic Nasa Fertilizer and NPK Fertilizer - Nunuk Helilusiatiningsih; Micko Widiyatmoyo (Publikasi Indonesia, 2022)
Vegetables that contain vitamins, minerals and fiber to maintain a healthy body. Green mustard is a horticultural crop commodity that is easy to cultivate and is widely consumed by the public because it has a good taste. The purpose of the study was to determine the response to development and production with the application of POC Nasa and NPK Mutiara fertilizer. The experiment was carried out in the rice fields of Sukoharjo Village, Kayen Kidul District, Kediri Regency. The location has an altitude of 91 m above sea level with a tropical climate with an average air temperature of 28 oC and a rainfall of 2,443 mm/year, allivial soil type with a pH of 5.5. The research method used a factorial randomized block design with 2 factors, the first factor was the concentration of liquid organic fertilizer consisting of 4 levels (K), the second factor was NPK fertilizer consisting of 4 levels coded D, repeated 3 times with 48 research plots. The results were analyzed by the F test, followed by the 5% BNT test and 5% DMRT if there was an effect. The results of this study can be concluded as follows: 1. There was an interaction between the concentration of POC Nasa and the dose of NPK on the variables observed for the number of leaves (21, and 28 days), leaf area (28 days), and wet weight per plant (28 days) and the best is K3D2 (POC 18 ml/L and NPK 6 gr/polybag) with 15, 31 leaves, 288 cm2 leaf area, and a wet weight of 163.87 grams/plant.